Sorarji, R. (ed.): “Philoponus and the Rejection of Aristotelian Science". IX y 253 páginas. Duckworth. Londres, 1987. ISBN: 0-7156-20089-4 - Fernández, Gonzalo (Gerión. Revista de Historia Antigua, 1988)
Sin resumen